Decentralized event-based leader-following consensus for a group of two-wheeled self-balancing robots - O.D. Ramírez-Cárdenas; J.F. Guerrero-Castellanos; J. Linares-Flores; S. Durand; W.F. Guerrero-Sánchez (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This paper deals with the development of a decentralized event-based control strategy applied to the leader-following consensus problem of a group of two-wheeled self-balancing robots so called mobile inverted pendulum (MIP). The MIP’s nonlinear mathematical model which includes the dynamics of the actuators is presented. Then, the model around an operating point is considered which allows to exploit the differential flatness property of the system, permitting a complete parametrization in terms of the flat output. Assuming that the vehicle network exchange information through a directed and strongly connected graph, a decentralized control law is designed, and an event-based algorithm is developed. Then each MIP decides, based on the difference of its current state and its latest broadcast state, when it has to send a new value to its neighbors. The stability of the complete system is carried out in the Lyapunov sense together with the ISS (Input-to-State Stability) approach. Numerical results show the advantages wrt information exchange between MIPs, as well as a good performance in the angular stabilization under two scenarios: regulation and tracking problem.